Using strong structuration theory to examine sustainability in a university setting - Stirk, Michelle V. (2021)
Given the increasing importance of the sustainability agenda, organisations are coming under pressure to demonstrate how they are contributing to improving sustainability. Organisations by themselves do not deliver outcomes; rather it is an organisation’s employees working as a collective who ultimately meet objectives and targets. The purpose of this research is to gain insights into how employees engage with sustainability in their daily activities and how they interact with control systems, either formal or informal, that are responsible for the delivery of sustainability in a Higher Education organisation. This study has collected and analysed interview data from employees to reveal the micro, meso and macro level forces that cause or prevent sustainability engagement. By understanding how, where, by whom and the extent to which users are influenced, this signposts potential tensions that exist. Addressing these tensions may result in better organisational sustainability engagement and therefore, better delivery of organisational sustainability goals, via the control systems. The research also illuminates the positive enablers of and influences on employee sustainability practices and action. Strong Structuration Theory (Stones, 2005) is used as a framework, to inform both the research design and assist in unpacking the empirical findings. The findings indicate that individuals are complex, and many contextual and disparate structures are considered when choosing to decide how to behave. The breadth and depth of the discussions support both the inter- and intra-disciplinary nature of sustainability. Combining the multi-dimensional characteristics of individuals and sustainability has meant the incorporation of several themes within this research, such as theology, adult learning and the significant influence of the media. This research has uncovered commonalities and patterns of thinking amongst employees’ interpretations of their own unique reality. For organisations that are pursuing sustainability focused goals and strategies, if suitably mobilised, this new knowledge has significant practical applications. The contribution of this research can assist in the development of better attuned organisational sustainability controls, and the delivery of increased sustainability-centred employee conduct.